MODEL ARSITEKTUR DAN KESESUAIAN FUNGSI JENIS-JENIS POHON DI CAGAR ALAM DAN TAMAN WISATA ALAM GUNUNG GAMPING SLEMAN - , FITRI APRIANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Natural Park is one of the green open space. The spatial of Natural park requires a harmonious combination between buildings and vegetation composition. Tree species selection that considering architecture aspect will increase the landscape function of the natural park. Gunung Gamping is one of the green open space area which became a natural tourism area in Ambarketawang, Sleman. This location often be used for ceremonial customs place and still be maintained of their authenticity, thus making identification of the trees species and arrangement of the trees species have not been well performed yet. Based on these conditions, there should be any identification of architectural models to determine the trees species and evaluate the suitability of the area to assess the function of the area with the vegetation structure as an effort to develop and optimize the green space area. This study was conducted in Wildlife Sanctuary and Natural Park Gunung Gamping. The Method of the research were tree inventory and trees species identification based on tree architecture models from sapling until tree and matching the tree criteria based on the expected function. The result of this study are from the inventory, there are 32 species of trees with 18 family and 12 tree architectural models. Those architecture models were: Aubreville, Macâlure, Troll, Cook, Scarrone, Kwan koriba, Corner, Roux, Petit, Rauh, Prevost and Attim. The evaluation of trees species based on architectural models and its function in each zone was still less appropriate. The addition and reduction of tree species to improve the site function is needed.